THE ROLE OF ISLAMIC RELIGIOUS EDUCATION IN THE FORMATION OF FAMILY AND CIVIL SOCIETY - AH.Mursyid (Tsaqofah : Jurnal Pendidikan Islam, 2022)
Family education is very important, as it enables families to establish and maintain proper relationships between family members, friends and others. Family education also provides knowledge, values and skills that are important for children's lives. Islamic religious education is an effort in the form of teaching, guidance and care for children so that when they finish their education they can understand, appreciate and practice the teachings of Islam and make it a way of life, both personal and community life. This writing aims to know and discuss the role of Islamic religious education in the formation of families and civil society. This writing method uses a literature study with a descriptive approach. It can be concluded that the role of Islamic religious education is: (1) the foundation in the family to shape the behavior and morals of children and know the limits of good and bad, (2) serves to form a human being who believes and is devoted to Allah SWT, (3) the main foundation and plays a role in moral education for the development of Indonesian society as a whole. Keywords: Islamic Religious Education, Family, Civil Society